Uji Presisi Kadar FE Pada Asi Metode Spektrofotometri Serapan Atom - Shafriani, Nazula Rahma (Jurnal Analis Laboratorium Medik, 2022)
One of the nutrients that babies need is iron (Fe). Iron content can be measured by atomic absorption spectrophotometry (AAS). This method is often used because it is simpler, more accurate and has high precision. This study was to determine iron levels and to determine precision of examination of iron levels in breast milk using AAS. The method of this research is the preparation of samples, tools, and materials, the manufacture of a standard solution of iron (Fe), and the calculation of the precision value of the examination of iron levels in breast milk. According to the findings, the three test groups' average Fe level was 1.1486 mg/L. This study's precision test was run based on repeatability. In this study, the precision test was conducted by measuring three groups of samples ten times. The precision test based on repeatability is declared acceptable by comparing the CV value obtained with CV-Horwitz, if the %CV obtained is less than CV-Horwitz, then the precision test based on repeatability is acceptable. Based on the measurements that have been made, CV (%) in test group A is 7.0690, test group B is 9.0686, test group C is 7.9807. These results indicate that the three test groups have CV % which is smaller than CV-Horwitz. Depending on the findings of the study, the validation of the technique for calculating Fe levels using AAS satisfies the standards for the approved value.